Molecular confirmation of the linkage between the rhizopus oryzae CYP51A gene coding region and its intrinsic voriconazole and fluconazole resistance - Macedo, Daiana (2018)
Rhizopus oryzae is the most prevalent causative agent of mucormycosis, an increasingly reported opportunistic fungal infection. These Mucorales are intrinsically resistant to Candida- and Aspergillus-active antifungal azole drugs, such as fluconazole (FLC) and voriconazole, respectively. Despite its importance, the molecular mechanisms of its intrinsic azole resistance have not been elucidated yet. The aim of this work was to establish if the Rhizopus oryzae CYP51 genes are uniquely responsible for intrinsic voriconazole and fluconazole resistance in these fungal pathogens. Two CYP51 genes were identified in the R. oryzae genome. We classified them as CYP51A and CYP51B based on their sequence similarity with other known fungal CYP51 genes. Later, we obtained a chimeric Aspergillus fumigatus strain harboring a functional R. oryzae CYP51A gene expressed under the regulation of the wild-type A. fumigatus CYP51A promoter and terminator. The mutant was selected after transformation by using a novel procedure taking advantage of the FLC hypersusceptibility of the A. fumigatus CYP51A deletion mutant used as the recipient strain. The azole susceptibility patterns of the A. fumigatus transformants harboring R. oryzae CYP51A mimicked exactly the azole susceptibility patterns of this mucormycete. The data presented in this work demonstrate that the R. oryzae CYP51A coding sequence is uniquely responsible for the R. oryzae azole susceptibility patterns.